SYNTHESIS AND CHARACTERIZATION OF SELENIUM NANO PARTICLES BY HIGH ENERGY BALL MILLING (HEBM) TECHNIQUE - J. Jamima; P. Veeramani; P. Kanagaraju; K. Kumanan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In present day, supplementation of extra minerals and vitamins is highly essential in commercial diets due to high productivity and to withstand the detrimental effects of different stresses. Selenium is one of essential trace minerals for better growth and productivity as well as anti-stressor in commercial broilers. Nano-selenium can effectively be synthesized through High Energy Ball Milling (HEBM) technique from its precursor, for use in commercial broilers as anti-stressor and to support multiple bodily functions. The prepared nano particle had 44.5 % of selenium as measured by Energy Dispersive X-ray (EDAX) analysis with the product yield of 50 g/hr. The chemical composition of sodium selenite powder was same as that of the original mega particle. The size of Se nano particle ranged from 37-85 nm as analyzed through Field Emission Scanning Electron Microscope (FESEM). X-Ray diffraction pattern confirmed that the synthesized Se nano particle was free of impurities and provided accurate information on the atomic arrangements. The Fourier Transform Infra-Red (FTIR) spectrum of synthesized nano particle source of selenium peaks was located at 3023.26, 2800.12, 2502.23, 2314.17, 1610.40 and 1413.30 cm-1 which showed chemical bonding in a target material. The zeta potential of nano selenium was -23.30 mV when analyzed through particle size analyzer. Se nano-particles could be successfully synthesized through High Energy Ball Milling method from its precursor and could be characterized for its quantity, size, shape, stability and purity. The synthesized Se nano-particles could be utilized for the conduct of biological trial in commercial broilers.